2021
DOI: 10.21037/qims-21-331
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional nuclear magnetic resonance spectroscopy: a complementary tool to multiparametric magnetic resonance imaging in the identification of aggressive prostate cancer at 3.0T

Abstract: Background: The limitations of the assessment of tumor aggressiveness by Prostate Imaging Reporting and Data System (PI-RADS) and biopsies suggest that the diagnostic algorithm could be improved by quantitative measurements in some chosen indications. We assessed the tumor high-risk predictive performance of 3.0 Tesla (3.0T) multiparametric magnetic resonance imaging (mp-MRI) combined with nuclear magnetic resonance spectroscopic sequences (NMR-S) in order to show that the metabolic analysis could bring out an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Several studies have shown that the differentiation between low-and high-risk cancer lesions by mpMRI, employing T 2 W MRI, DW imaging, and DCE imaging, is enhanced by adding 1 H-MRSI data. [20][21][22]24 With our high AUC values for this differentiation, we expect even more enhancement by adding an MCR analysis.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…Several studies have shown that the differentiation between low-and high-risk cancer lesions by mpMRI, employing T 2 W MRI, DW imaging, and DCE imaging, is enhanced by adding 1 H-MRSI data. [20][21][22]24 With our high AUC values for this differentiation, we expect even more enhancement by adding an MCR analysis.…”
Section: Discussionmentioning
confidence: 84%
“…Prostate MRSI studies of PCa patients commonly demonstrate a correlation between GSs and metabolite ratios and find significant differences between low-and high-risk cancer lesions. 3,20,21,24,[51][52][53] However, the overlap of ratio values between different risk groups hampers the assignment of individual cases to particular risk groups. Several studies have shown that the differentiation between low-and high-risk cancer lesions by mpMRI, employing T 2 W MRI, DW imaging, and DCE imaging, is enhanced by adding 1 H-MRSI data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The early decrease in citrate is therefore due to both changes in cellular function and in the organization of the tissue, but may also decrease in prostatitis, when the choline level increases proportionally to tumor cell proliferation or in the case of necrosis, a phenomenon which is mainly visible in undifferentiated tumors, particularly with a high Gleason grade ( 39 ). Indeed, the use of metabolite concentrations may even be more pertinent than simple ratios, commonly used in the literature, as shown in the recent study by Deal et al ( 40 ) in which spectroscopic data showed that the choline concentration was significantly higher in aggressive disease. Moreover, in their study, the predictive model of tumor aggressiveness combining mpMRI and 3D MRS was better than the mpMRI model alone.…”
Section: Discussionmentioning
confidence: 99%